PHYSICO-CHEMICAL ALTERATIONS IN TAPHRINA DEFORMANS INFECTED PEACH LEAVES - Y. P. SHARMA2, R. C. SHARMA1 AND (Indian Phytopathology, 2002)
Physico-chemical changes in Prunus persica leaves infected with Taphrina deformans were studied. Marked increase in the weight of fresh and dry leaves, moisture, ash and protein was recorded. Total chlorophyll, chlorophyll a, chlorophyll b, molar ratio of chlorophyll a and b were less in diseased leaves but had higher quantities of nitrogen, phosphorus and calcium. Amount of magnesium was less in diseased leaves